Prognostic significance of ERCC1 expression in postoperative patients with gastric cancer - Wang, Jian; Zhou, Xi-Qiao; Li, Jing-Ying; Cheng, Jian-Feng; Zeng, Xiao-Ning; Li, Xiao; Liu, Ping (Chinese Journal of Cancer Research; Vol 26, No 3 (June 01, 2014): Chinese Journal of Cancer Research, 2014)
Aim: This study explored the correlation between the expression of excision repair cross-complementation group 1 (ERCC1) and the prognosis of gastric cancer patients. Methods: From January 2005 to December 2008, 605 patients who underwent radical surgery in The First Affiliated Hospital of Nanjing Medical University were enrolled. We conducted the follow-up every 6 months and its contents included a comprehensive medical history, tumor markers and abdominal ultrasound or CT and other imaging findings. Deadline was April 30, 2013 and follow-up time between 51 to 91 months. Survival time is calculated from the date of diagnosis to death or last follow-up date. Immunohistochemistry (IHC) was used to assess the expression of ERCC1 in resected samples. The relationship between ERCC1 expression and survival of patients was investigated. The comparison of count data were analyzed by Chi-square test. Median survival time (MST) and the 5-year survival rate were calculated by life table analysis. The Kaplan-Meier curves were used for survival analysis. Results: ERCC1 expression was positive in 412 patients (68.1%). There is no significant difference between ERCC1-positive group and ERCC1-negative group in terms of the MST and 5-year survival rate (P=0.455). The MST and 5-year survival rate have no significant difference (P=0.162) between group with chemotherapy and group with no chemotherapy in patients with ERCC1-positive expression. However, the MST and 5-year survival rate in patients with ERCC1-negative expression benefited more from with chemotherapy (P=0.019). The ERCC1-positive patients survived longer than those ERCC1-negative patients (P=0.183) in subgroup with no adjuvant chemotherapy. In the subgroup analysis, ERCC1 expression had no significant relationship with overall survival in patients with stage II or III gastric cancer (P>0.05). Conclusions: ERCC1 might be a good prognostic factor for the patients of gastric cancer after radical resection. Patients with ERCC1-negative expression could benefit more from adjuvant chemotherapy.